2016
DOI: 10.1111/acel.12461
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide mononucleotide supplementation reverses vascular dysfunction and oxidative stress with aging in mice

Abstract: SummaryWe tested the hypothesis that supplementation of nicotinamide mononucleotide (NMN), a key NAD + intermediate, increases arterial SIRT1 activity and reverses age‐associated arterial dysfunction and oxidative stress. Old control mice (OC) had impaired carotid artery endothelium‐dependent dilation (EDD) (60 ± 5% vs. 84 ± 2%), a measure of endothelial function, and nitric oxide (NO)‐mediated EDD (37 ± 4% vs. 66 ± 6%), compared with young mice (YC). This age‐associated impairment in EDD was restored in OC by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
237
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 306 publications
(266 citation statements)
references
References 51 publications
(138 reference statements)
15
237
3
Order By: Relevance
“…NAD + declines with age (47,51), and supplementation with NAD + precursors can delay aging, liver disease, and vascular dysfunction (52)(53)(54). NAD + precursors, such as nicotinamide riboside, can be used safely in humans (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…NAD + declines with age (47,51), and supplementation with NAD + precursors can delay aging, liver disease, and vascular dysfunction (52)(53)(54). NAD + precursors, such as nicotinamide riboside, can be used safely in humans (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 8 weeks of NMN supplementation restored arterial SIRT1 activity and ameliorated age-associated endothelial dysfunction and large elastic artery stiffening in mice. These improvements restored nitric oxide bioavailability, reduced oxidative stress, and promoted complete or partial normalization of structural proteins in the arterial wall (de Picciotto et al, 2016). …”
Section: Interventions To Prevent Age-related Nad Declinementioning
confidence: 99%
“…There is, however, some evidence in support of other activators of the SIRT-1 network, such as nutraceuticals that boost NAD + (the cellular trigger for SIRT-1 activity). For example, supplementation with nicotinamide mononucleotide (NMN), a metabolic precursor to NAD + , restores endothelial function and decreases arterial stiffness (de Picciotto et al, 2016), and clinical trials investigating the effects of nicotinamide riboside (NR, a similar compound found in milk and yeast-derived foods) on various physiological parameters, including arterial function, are currently underway (clinicaltrials.gov).…”
Section: Nutritional Factors and Interventionsmentioning
confidence: 99%